Comparison Method of PI, PID and Fuzzy Logic Controller to Maintain Speed Stability in Single Phase Induction Motors - Irianto, Irianto; Murdianto, Farid Dwi; Sunarno, Epyk; Proboningtyas, Dewinta Dwi (INTEK: Jurnal Penelitian, 2021)
Induction motor speed control is one of the operating conditions that is often used so that feedback with a low error rate is required. To fulfill this, PI and PID controls have been implemented for single phase induction motors. This control has parameters, namely Kp, Ki and Kd. PI and PID controls can cover a variety of desired response conditions, but these controls still have weaknesses in the tuning process. The tuning process used still has a fairly large error value. So in this case we need an intelligent control to meet the desired motor speed response specifications. The performance of motor speed regulation was evaluated using a comparison between PI and PID control with Fuzzy in a closed loop. With a setting point of 1500 rpm, for PI control, with Kp = 7.32 and Ki = 0.005 can produce motor speeds up to 1499. While PID control with Kp = 0.95, Ki = 0.005 and Kd = 0.04 can produce similar speeds. 1492. Fuzzy control can produce an output of 1490 rpm. Fuzzy control is able to produce a settling time of 0.25 seconds and a steady error of 0.67%.